2020
DOI: 10.1111/jfb.14428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light intensity and photoperiod on embryonic development, survival and growth of threatened catfish Ompok bimaculatus early larvae

Abstract: Larval growth and survival of catfishes are largely influenced by the various biotic and abiotic factors. The present study investigated the effect of different light intensities and photoperiods on growth and survival of Ompok bimaculatus larvae. Three separate trials of 21 days each were carried out in an aquarium tank. The first trial investigated the embryonic changes (based on hatching rate and time) upon exposure to varied light intensity (0, 300, 500, 900 and 1200 lx) and photoperiodic regime (24l:0d, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Light intensity is a crucial environmental factor that influences aquacultural water quality, such as temperature, pH, and levels of DO, ammonia, nitrite and total phosphorus [9,10]. In this research, as expected, low-intensity light significantly down-regulated the pH, DO and ammonia content of aquaculture water, but up-regulated the levels of nitrite and total phosphorus.…”
Section: Discussionsupporting
confidence: 74%
“…Light intensity is a crucial environmental factor that influences aquacultural water quality, such as temperature, pH, and levels of DO, ammonia, nitrite and total phosphorus [9,10]. In this research, as expected, low-intensity light significantly down-regulated the pH, DO and ammonia content of aquaculture water, but up-regulated the levels of nitrite and total phosphorus.…”
Section: Discussionsupporting
confidence: 74%
“…Larval development and growth rates of zebrafish can be significantly impacted by light conditions (Villamizar et al ., 2014), and growth rate and aggression between individuals have been shown to improve with lower light intensity in other species too (Almazán‐Rueda et al ., 2004; Arambam et al ., 2020; Boeuf & Le Bail, 1999; Rahman et al ., 2020; Tian et al ., 2015). Recent studies have focused on the effects of other aspects of light conditions on captive fish, such as the effects of acute bursts of light from photography (camera flashlight) (Knopf et al ., 2018), but despite the importance of light conditions, and the relationship with PE which may provide shelter and shade from lights, most studies exploring PE tend to ignore light and provide very few details outside of photoperiod.…”
Section: Towards a More Refined Understanding Of Pementioning
confidence: 99%
“…Epidemiological studies and substantial experimental evidence have repeatedly reported that changes in the light/dark cycles have been closely associated with various metabolic disorders (Rutter et al, 2002;Maury et al, 2010). In aquatic animals, the light/dark cycle acts as an important biological factor that influences the entire life cycle from embryonic development to sexual maturation (Downing and Litvak, 2001;Migaud et al, 2010;Arambam et al, 2020). In recent years, growing evidence has shown that the effects of the light/dark cycle on various species are diverse, some have a natural preference for the dark environment while some have an improved physiological state under high-light intensity (Serra et al, 1999;Ruchin, 2006;Li et al, 2021b;Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%